Atlas of Shear Zone Structures in Meso-scale - Mukherjee, Soumyajit; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Study of structures associated with shear zones is a crucial aspect to understand the deformation mechanism associated with such zones. Shear zones have been emphasized since it will lead to many latest applied studies such as radioactive waste disposal, groundwater flow etc. For the sake of brevity, research papers cannot show all possible variation in structures found in shear zones. The proposed book aims to present some of these structures in great details with attractive colour photographs. Each photograph will have a comprehensive caption.
S-C shear fabric as ductile shear sense indicators -- Sheared clasts -- Folds in shear zones -- Brittle shear sense indicators -- Boudins in shear zones -- Fractures in shear zones.
Keywords: Geography; Geology, Structural; Mineralogy; Earth Sciences; Structural Geology; Mineralogy